ESG Investment, AI Risk Management, and Ethical Compliance in Strengthening Financial Stability - Wei Yinze, Xian; Chen Wuy, Ling (Journal Economic Business Innovation, 2025)
Purpose: The study engages in the empirical examination of the direct and mediated influence of ESG investment, AI for risk management and ethical compliance on financial stability. It aims to find out the extent that transparency quality of firms is an underlying factor for such modern strategic practices in making stability, investor confidence and market trust to be achieved.Method: Information was collected from the senior managers through a structured questionnaire using quantitative approach. The relations proposed were estimated through regression techniques and mediation analysis examining the direct paths; and the significance of indirect effects using the SPSS Proces macro.Findings: ESG investment, AI risk management and ethical compliance positiviely have a significant direct on financial stability as suggested by the results. The analysis also suggests strong support for full mediation of both relationships by transparency. This finding implies that information disclosure and communication are where the welfare effects of strategic behavior have been mostly exploited by reducing information asymmetry for stakeholders and by increasing their trust through transparent quarterly reporting.Originality/value: This study presents the first comprehensive model that investigates in an integrated manner the synergy of three significant governance drivers. Its main theoretical contribution is to demonstrate, empirically, what I call transparency not just as an outcome but also as the primary mediating conduit translating drivers of real corporate action into observable financial condition and so providing a unified explanation for fragmented results.Implications: The results present a clear strategic roadmap for corporate leadership, stressing the imperative to combine sustainability, technological governance and ethics supported by radical transparency. To regulators, the research suggests that it is in the public interest to maintain disclosure regimes designed to promote market efficiency and resiliency through making corporate conduct observable and credible.